2009
DOI: 10.1001/archinternmed.2009.71
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Pharmacist Intervention to Reduce Morbidity in Patients 80 Years or Older

Abstract: If implemented on a population basis, the addition of pharmacists to health care teams would lead to major reductions in morbidity and health care costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
614
10
12

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 495 publications
(683 citation statements)
references
References 34 publications
25
614
10
12
Order By: Relevance
“…Gillespie et al identified 2.6 DRPs per patient, all of which were put forward and the physicians made adjustments for 69% of the DRPs while 23% of the suggestions were rejected (16). Blix et al identified 3.2 DRPs per patient and 74% of the identified DRPs were put 11 forward (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gillespie et al identified 2.6 DRPs per patient, all of which were put forward and the physicians made adjustments for 69% of the DRPs while 23% of the suggestions were rejected (16). Blix et al identified 3.2 DRPs per patient and 74% of the identified DRPs were put 11 forward (26).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in staffing of clinical pharmacist at United States hospitals reduced hospital drug costs (15). In Sweden, a clinical pharmacy service resulted in a decrease in drug related hospital readmissions and health care costs (16).…”
Section: The Process Of Identifying Solving and Preventing Drug Relamentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Twenty-one studies applied to general populations, largely older adults and together included 10 445 patients. 1,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] Four studies applied to unique populations. 2,3,75,76 Twenty-nine studies were based in the United States, while the rest were in other nations.…”
Section: Population and Contextmentioning
confidence: 99%
“…The clinical pharmacy process involves identifying potential and actual DRPs, resolving actual DRPs and preventing potential DRPs. Previous studies have demonstrated that clinical pharmacy services for in-patients reduce the number of drug-related problems [12], the length of stay [13][14][15][16], costs [13,[16][17], adverse drug reactions [18], rates of readmission [14][15] and rates of drug-related readmission [19].…”
Section: Introductionmentioning
confidence: 99%